Implementasi Metode Weighted Product untuk Rancangan Sistem Pendukung Keputusan Pemilihan Saham Terbaik - Robby Yuli Endra; Yuthsi Aprilinda; Feri Jumaidi (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2022)
This decision support system for selecting the best stocks in the financial sector aims to make it easier for investors to determine stocks with the best categories in terms of the fundamentals of these stocks. With a system that can select and determine healthy stock fundamentals, of course, investors can easily compare what stocks are worth investing in. This study uses the financial ratios of a stock (issuer) listed on the Indonesia Stock Exchange as a comparison which is calculated using the Wighted Product method consisting of Net Profit Margin (NPM), Return on Equity (ROE), Earning per share (Eps), Price to Earning Ratio (PER) and Debt to Equity Ratio (DER) Price Book Value (PBV). The data used in this study is secondary data from the banking financial statements for the 2021 period taken in the final quarter. Based on the research that has been done using the Wighted Product method, it can be concluded that the Wighted Product method can display and calculate stocks or alternatives with the best categories starting from the smallest to the largest values based on existing criteria. The contribution to this research is to help investors choose the best stocks with the output provided by this Decision Support System with the Weighted Product Method so as to minimize losses.